2002
DOI: 10.1021/la0114979
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Brush Layers Studied by Surface Forces Measurement:  Dependence on pH and Salt Concentrations and Scaling

Abstract: Interactions between opposed brush layers of polyelectrolytes ionized poly(L-glutamic acid) (PLGA) or poly(L-lysine) (PLL) in water were directly investigated using surface forces measurement. The brush layers were prepared by the Langmuir-Blodgett deposition of amphiphiles bearing PLGA (degree of polymerization n ) 21, 44, and 48) or PLL (n ) 41 and 52) as hydrophilic groups. The density of polyelectrolyte chains was around 0.4 chain/nm 2 . Surface force profiles, consisting of a long-range electrical double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 50 publications
5
77
1
Order By: Relevance
“…Similar results have been reported by Matsuoka [23] and Kurihara. [24] Negligible change was also observed between the swelling structure of poly(MPC) facing a pure D 2 O and a NaCl deuterium oxide solution, as shown in Figure 1 (c) and (d). In this case, another mechanism should be explained.…”
Section: Resultsmentioning
confidence: 79%
“…Similar results have been reported by Matsuoka [23] and Kurihara. [24] Negligible change was also observed between the swelling structure of poly(MPC) facing a pure D 2 O and a NaCl deuterium oxide solution, as shown in Figure 1 (c) and (d). In this case, another mechanism should be explained.…”
Section: Resultsmentioning
confidence: 79%
“…Similar results have been reported by Matsuoka [9,10], Kurihara [11], and Tran. [12] Huck et al reported the swelling behavior of the poly(METAC) brush in solution observed by AFM. [13] They suggested that thickness of brush decreased at much lower external salt concentrations than the concentration of chemically charged monomers of the chains.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the size of features in the SFM images matches exactly with the calculated area/molecule deposited with the LB trough further supporting an average molecular weight of the comb molecules as being around 130 kDa. Some research into creating dense layers via amphiphilic copolymer LB assembly has been performed in the past [26][27][28][29][30][31][32][33][34][35], but we have shown that multi-molecular micellation (creating structures > 100 nm) has been largely prevented through controlling polymer chain architecture. Such films could potentially be used as ultrathin size-selective nanofiltration films for sensor applications, templates for nanolithography, or an environmentally acceptable way to tune the physical and chemical properties of a flat surface.…”
Section: Preparation Of Langmuir-blodgett (Lb) and Langmuir-schäfer (mentioning
confidence: 96%